Emerging therapeutic strategies for transplantation-induced acute kidney injury: protecting the organelles and the vascular bed. (3rd June 2019) - Melis, Nicolas; Thuillier, Raphael; Steichen, Clara; Giraud, Sebastien; Sauvageon, Yse; Kaminski, Jacques; Pelé, Thomas; Badet, Lionel; Richer, Jean Pierre; Barrera-Chimal, Jonatan; Jaisser, Frédéric; Tauc, Michel; et al.
ABSTRACT: Introduction : Renal ischemia-reperfusion injury (IRI) is a significant clinical challenge faced by clinicians in a broad variety of clinical settings such as perioperative and intensive care. Renal IRI induced acute kidney injury (AKI) is a global public health concern associated with high morbidity, mortality, and health-care costs. Areas covered : This paper focuses on the pathophysiology of transplantation-related AKI and recent findings on cellular stress responses at the intersection of 1. The Unfolded protein response; 2. Mitochondrial dysfunction; 3. The benefits of mineralocorticoid receptor antagonists. Lastly, perspectives are offered to the readers. Expert opinion : Renal IRI is caused by a sudden and temporary impairment of blood flow to the organ. Defining the underlying cellular cascades involved in IRI will assist us in the identification of novel interventional targets to attenuate IRI with the potential to improve transplantation outcomes. Targeting mitochondrial function and cellular bioenergetics upstream of cellular damage may offer several advantages compared to targeting downstream inflammatory and fibrosis processes. An improved understanding of the cellular pathophysiological mechanisms leading to kidney injury will hopefully offer improved targeted therapies to prevent and treat the injury in the future.